A revision of the patagonian predaceous midge genus Borkenthelea Spinelli and Grogan (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2001)
A revision of the Patagonian predaceous midge genus Borkenthelea Spinelli and Grogan revealed three undescribed species that we describe and illustrate as new species: Borkenthelea quatei, from Argentina; B. harii, from Argentina and Chile; and B. nerudai, from Chile. A key is provided for the recognition of males and females of the four species in this genus.